EDUCATION AND WORKSHOP ON INTEGRATING DEEP LEARNING AND GAME-BASED LEARNING IN DEVELOPING DIGITAL EDUCATION CARDS FOR HIGH SCHOOL TEACHERS IN EAST ACEH - Okhaifi Prasetyo; Hasby Hasby; Muhammad Khalil (Universitas Airlangga, 2025)
High school teachers in East Aceh face the challenge of limited skills in integrating technology, deep learning approaches, and game-based learning (GBL) strategies into teaching media. This condition results in learning that tends to remain conventional and less contextual to 21st-century needs. This community service activity aims to increase teacher capacity through education and workshops in developing digital educational cards based on local values ​​using the Technological Pedagogical Content Knowledge (TPACK) framework. The activity was carried out at SMAN Unggul East Aceh for three days and involved 30 teachers from various subjects. The methods used included providing conceptual material, direct practice, collaborative mentoring, and evaluation through pretests and posttests, observations, and satisfaction questionnaires. All data were analyzed descriptively to describe improvements in participant knowledge, skills, and satisfaction. The results showed an increase in teacher understanding based on the average posttest score, which increased from 5.41 to 8.65, and the participant satisfaction level reached 4.75 on a scale of 5. The concrete product, in the form of interactive digital educational cards, produced by teachers demonstrated the ability to integrate local values ​​into learning. This program is considered successful in creating a participatory, reflective, and creative learning atmosphere, and is recommended to be continued through ongoing mentoring and the formation of a teacher practice community.